HUBUNGAN ANTARA INTENSITAS KOMPETISI PASAR DAN SISTEM KONTROL INTERAKTIF PADA KINERJA ORGANISASI - Sutoyo, Sutoyo Sutoyo (Jurnal Bulletin, 2018)
Abstract: The Relationship between Intensity of Market Competition and Interactive Control System on  Organizational Performance. The purpose of this study is to investigate the relationship between intensity of market competition, interactive control system and organizational performance in manufacturing companies in Central Java Indonesia. The research data was collected from a survey of financial directors / managers or accounting / manager accounting manufacturing companies in Central Java, Indonesia. 529 questionnaires were distributed, 145 could not be found because of their busy schedule and 384 questionnaires were returned, 19 did not fulfill the requirements, so 365 respondents were used in data analysis. This study uses the Structural Equation Model (SEM) and uses AMOS 19 Software. The findings of this study indicate that the relationship between the intensity of market competition and interactive control systems has a positive and significant relationship. In addition, interactive control systems and organizational performance also have a significant positive relationship. Abstrak: Hubungan antara Intensitas Persaingan Pasar dan Sistem Kontrol Interaktif pada Kinerja Organisasi. Tujuan penelitian ini adalah untuk menyelidiki hubungan antara intensity of market competition, interactive control system dan organizational performance di perusahaan manufaktur di Jawa Tengah Indonesia. Data penelitian dikumpulkan dari survei direktur/manajer keuangan atau kontroller/manajer akuntansi perusahaan manufaktur di Jawa Tengah Indonesia. 529 kuesioner dibagikan, 145 tidak bisa ditemui karena kesibukannya dan 384 kuesioner dikembalikan, 19 tidak memenuhi syarat, sehingga 365 responden yang digunakan dalam analisis data. Penelitian ini menggunakan Structural Equation Model (SEM) dan menggunakan AMOS 19 Software. Temuan dari penelitian ini menunjukkan bahwa hubungan antara intensitas persaingan pasar  dan sistem pengendalian interaktif memiliki hubungan positif dan signifikans. Selain itu, sistem pengendalian interaktif dan kinerja organisasi juga memiliki hubungan positif signifikan. Kata Kunci: intensity of competition market, interactive control system,                        Organizational performance, contingency theory